Hyaluran-itaconic acid-glutaraldehyde films for biomedical applications: Preliminary studies - Calles, Javier Adrián (2015)
New hyaluronic acid?itaconic acid films were synthesized as potential materialswith biomedical applications. In this work, we explored the homogeneous crosslinkingreactions of hyaluronic acid using glutaraldehyde in the presence ofitaconic acid and triacetin as plasticizers.Biomechanical properties were assessed in terms of stability by measuringswelling in aqueous environments, investigating wettability using contact angletests and evaluating bioadhesive performance. The ductility of the materialswas evaluated through stress-strain measurements and the morphology wasexplored by scanning electron microscopy.The results show that the incorporation of itaconic acid improved most of thedesirable properties, increasing adhesiveness and reducing wettability andswelling. The use of triacetin enhanced the strength, bioadhesiveness andductility of the material.